218k views
2 votes
.3y + 3 (1 - y - y = 6​

User Ashlyn
by
4.7k points

1 Answer

4 votes

Answer:

sorry it's too long

Explanation:

Simplifying

3y + 3(1 + -1y) + -1y = 6

3y + (1 * 3 + -1y * 3) + -1y = 6

3y + (3 + -3y) + -1y = 6

Reorder the terms:

3 + 3y + -3y + -1y = 6

Combine like terms: 3y + -3y = 0

3 + 0 + -1y = 6

3 + -1y = 6

Solving

3 + -1y = 6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.

3 + -3 + -1y = 6 + -3

Combine like terms: 3 + -3 = 0

0 + -1y = 6 + -3

-1y = 6 + -3

Combine like terms: 6 + -3 = 3

-1y = 3

Divide each side by '-1'.

y = -3

Simplifying

y = -3

User MJegorovas
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.